Pengaruh Entomopatogen Metarhizium sp. dan Beauveria bassiana untuk Mengendalikan Hama Thrips sp. pada Tanaman Acacia crassicarpa - Carlos Tandri; Agus Prijono (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2026)
Nursery Department is the department responsible for ensuring the success of Acacia crassicarpa plants in the early stages before being planted in the planting area. One of the challenges faced by the Nursery Department is the attack of Thrips sp. pests which greatly threaten the quality and quantity of seedling production. Therefore, it is necessary to test the effect of entomopathogen Metarhizium sp. and Beauveria bassiana in overcoming Thrips sp. pest attacks. This research aims to determine the effect of using entomopathogen, both Metarhizium sp. and Beauveria bassiana, in overcoming the severity of Thrips sp. pest attacks and to find out whether it is true that Thrips sp. found dead are actually infected by entomopathogen. This research was carried out using a Randomized Complete Block Design (RCBD) method with a further test of the Least Significant Difference (LSD) follow-up test. The number of treatments in this study consisted of 6 treatments where each treatment was repeated 3 times. The parameters observed were the severity of Thrips sp. pest attacks and the percentage of Thrips sp. pests found dead infected by entomopathogens. The results of the study showed that entomopathogens, both Metarhizium sp. and Beauveria bassiana, showed a very significant effect on controlling the severity of Thrips sp. pest attacks. And Thrips sp. that were found dead were also proven to have died due to being infected by the entomopathogens Metarhizium sp. and Beauveria bassiana.